Inferential comprehension of 3–6 year olds within the context of story grammar: a scoping review. Issue 6 (24th July 2015) - Filiatrault‐Veilleux, Paméla; Bouchard, Caroline; Trudeau, Natacha; Desmarais, Chantal
Abstract Background The ability to make inferences plays a crucial role in reading comprehension and the educational success of school‐aged children. However, it starts to unfold much earlier than school entry and literacy. Given that it is likely to be targeted in speech language therapy, it would be useful for clinicians to have access to information about a developmental sequence of inferential comprehension. Yet, at this time, there is no clear proposition of the way in which this ability develops in young children prior to school entry. Aims To reduce the knowledge gap with regards to inferential comprehension in young children by conducting a scoping review of the literature. The two objectives of this research are: (1) to describe typically developing children's comprehension of causal inferences targeting elements of story grammar, with the goal of proposing milestones in the development of this ability; and (2) to highlight key elements of the methodology used to gather this information in a paediatric population. Methods & Procedures A total of 16 studies from six databases that met the inclusion criteria were qualitatively analysed in the context of a scoping review. This methodological approach was used to identify common themes and gaps in the knowledge base to achieve the intended objectives. Main Contribution Results permit the description of key elements in the development of six types of causal inference targeting elements of story grammar in children between 3 and 6 years old. Results also demonstrate the various methods used to assess this ability in young children and highlight particularly interesting procedures for use with this younger population. Conclusions These findings point to the need for additional studies to understand this ability better and to develop strategies to stimulate an evidence‐based developmental sequence in children from an early age.